Influence of sedimentation and detrital clay grain coats on chloritized sandstone reservoir qualities: Insights from comparisons between ancient tidal heterolithic sandstones and a modern estuarine system. (September 2019) - Virolle, Maxime; Brigaud, Benjamin; Luby, Sylvain; Portier, Eric; Féniès, Hugues; Bourillot, Raphaël; Patrier, Patricia; Beaufort, Daniel
Abstract: Authigenic clay coats (mostly Fe-rich chlorite coats) affect sandstone reservoir qualities by inhibiting quartz overgrowth during burial diagenesis, preserving both porosity and permeability. It is still unclear what initial mineralogical assemblages and initial sedimentation conditions produce chloritized sandstone reservoirs, which is important for sandstone reservoir quality prediction. For this purpose, better link facies with chlorite coat occurences could be useful. To address these questions, sedimentological, petrographical and mineralogical analyses were carried out from sand and sandstones cores for both a deeply buried Permian estuarine sandstone reservoir (Australia) and the Gironde estuary (France). Comparisons reveal similar sedimentary facies and vertical facies associations (from a muddy bottom to cross-stratified sandier packages and to a muddy top), indicative of tidal sand bars deposited in a mud-rich estuary. These criteria can be useful for recognizing tidal deposits when describing cores. X-ray diffraction and Scanning Electron Microscope (SEM) analysis show that detrital clay minerals are composed of illite, smectite, kaolinite and chlorite while clay assemblage differs in the Permian reservoir with dickite or an illite-rich illite/smectite mixed layer (I/S). Coats are either composed of detrital clays minerals (Gironde) or Fe-rich chlorite crystals (Permian). Transformations of detrital clays into other clay minerals (such as berthierine, precursor to Fe-rich chlorite) during eogenesis can initiate well-crystallized Fe-rich chlorite formation during burial diagenesis. Detrital minerals and detrital clay grain coats observed in the Gironde estuary could be the prerequisite initial conditions for generating authigenic Fe-rich chlorite coats in estuarine sandstones during burial. This is partly due to the initial clay fraction content of 15-20%, part of which forms detrital clay grain coats. Our main conclusion shows that facies from the middle to the upper tidal sand bar at the top of the transgressive cycle were probably uncemented during burial, and might be good candidates during reservoir exploration. Highlights: Sediments of the P.U.C.H.F ( Australia) were deposited in a paleo-estuary very similar to the present-day Gironde estuary. Best reservoir facies are located from the middle to the upper sand bar areas deposited in the outer estuarine tidal bars. Detrital clay minerals from the Gironde might promote precursor clay-mineral formation to Fe-rich chlorite coats. Sandstones deposited at the top of the transgressive sequence .might be good candidates for reservoir exploration. Ideal initial conditions for reservoir formation can be a maximum clay content of 20–25 wt%, with coated grain content of 15–20% and coat coverage of about 10%..